“The Land Is Mine” (Leviticus 25:23): Reimagining the Jubilee in the Context of the Palestinian-Israeli Conflict - Joseph, Simon J. 1966- (2020)
The Jubilee tradition commemorates the release of slaves, the remission of debt, and the repatriation of property, a “day” of physical and spiritual restoration. The Jubilee tradition—originating in a constitutional vision of ancient Israel periodically restoring its ancestral sovereignty as custodians of the land—became a master symbol of biblical theology, a powerful ideological resource as well as a promise of a divinely realized future during the Second Temple period, when the Qumran community envisioned an eschatological Jubilee and the early Jesus tradition remembered Jesus’ nonviolence in Jubilee-terms. Jubilee themes can also be identified in ideals inscribed in the founding of America, the Abolition movement, the Women’s Liberation Movement, the Civil Rights movement, and Liberation Theology. This study seeks to extend the exploration of Jubilee themes by adopting a comparative methodological approach, re-examining Jubilee themes in the context of the contemporary Palestinian-Israeli conflict, where the dream of Peace in the Middle East continues to play out in predominantly politicized contexts.
Keywords: Liberation; Palestinian/Israeli Conflict; Peace & Nonviolence; Jubilee Year